2020
DOI: 10.3389/fsufs.2020.00030
|View full text |Cite
|
Sign up to set email alerts
|

Organic Amendments Alleviate Salinity Effects on Soil Microorganisms and Mineralisation Processes in Aerobic and Anaerobic Paddy Rice Soils

Abstract: Sea-water level rise leads to increased saltwater intrusion causing soil salinity on arable land with negative effects on soil microbial processes. Organic amendments are known to reduce the effects of salinity on soil microorganisms, therefore positively influencing microbial activity and nutrient cycling. However, the extent of this effect in paddy rice soils under aerobic compared to anaerobic conditions is unknown. Consequently, benefits of organic matter addition on carbon (C) and nitrogen (N) mineralisat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(44 citation statements)
references
References 65 publications
(124 reference statements)
1
41
0
2
Order By: Relevance
“…Decreased survival of microorganisms because of increased salinity and moisture stress prevailing in March–April at the experimental site was mainly responsible for lower MBC values after wheat compared to sorghum harvest. This finding conforms with others 34 , 48 those recorded lower values of MBC in the soil after harvest of wheat compared to sorghum in saline soils. The 100CWR saline-water irrigation imported more salts compared to deficit saline-water irrigation (60 and 80CWR) and showed lower values of MBC.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Decreased survival of microorganisms because of increased salinity and moisture stress prevailing in March–April at the experimental site was mainly responsible for lower MBC values after wheat compared to sorghum harvest. This finding conforms with others 34 , 48 those recorded lower values of MBC in the soil after harvest of wheat compared to sorghum in saline soils. The 100CWR saline-water irrigation imported more salts compared to deficit saline-water irrigation (60 and 80CWR) and showed lower values of MBC.…”
Section: Discussionsupporting
confidence: 93%
“…Measuring the activities of phosphatase, dehydrogenase, urease and glucosidase serve as an early indicator of changes in soil health of saline soil brought under cultivation 43 , 48 . Activities of these enzymes increased with a gradual decline in EC e after every crop cycle.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies reported a significant increase in the soil microbial and enzymatic activities as a result of organic matter incorporation. The incorporation of organic amendments resulted in enhanced enzymatic activities [31,33,140,161,164,172], microbial biomass C [32,143,161,164,173], microbial biomass N [32,161], soil microbial activity as expressed by basal respiration [32,174], and nematode abundance [143]. However, the response of microbial and enzymatic activities to organic amendments differs depending on the kinds of amendments, rates of incorporation, the types of crops grown, etc.…”
Section: Effects Of Organic Amendments On the Physical Chemical Andmentioning
confidence: 99%
“…Thus, although the analyzed soil was not included in the saline soil classes, that is, EC <2 dS m −1 (Castro & dos Santos, 2020), the bacterial community in the natural and exclusion treatments may drive nutrient cycles more efficiently at lower salt concentrations because of their increased soil organic matter and CN availability (Table 1). Elevated salt concentrations in the soil can change the nutrient availability for plants and microbial communities, and it affects the quantity and quality of soil organic matter (Wichern, Islam, Hemkemeyer, Watson, & Joergensen, 2020). In addition, previous studies have shown that salt contents influenced the size and the activity of soil microbial biomass, which in turn plays an important role in soil biogeochemical cycles (Mavi, Sanderman, Chittleborough, Cox, & Marschner, 2012; Rietz & Haynes, 2003; Tripathi et al, 2006).…”
Section: Discussionmentioning
confidence: 99%